The frequency of labial-velar stops in northern sub-Saharan Africa - (:unkn) unknown (My University, 2018)
Cross-linguistically, labial-velar stops are rather rare, but they are known to be common in the phonological inventories of many genealogically diverse languages spoken in northern sub-Saharan Africa. Using quantitative data, this paper shows that the distribution of the lexical frequency of labial-velar stops is very uneven in the languages of this area. First, we can distinguish between languages with low frequency of labial-velar stops in the lexicon and languages with high lexical frequency of labial-velar stops. Importantly, the spatial distribution of the two groups is not random. There are three hotbeds of high lexical frequency of labial-velar stops and a peripheral area of low lexical frequency. Second, we show that within individual languages significant differences in the frequencies of labial-velar stops exist between the so-called basic vocabulary and the lexicon as the whole, which we take as indirect evidence for the hypothesis that labial-velar stops are more frequent in the "expressive" parts of the lexicon, such as ideophones.
Keywords: African Research